2008
DOI: 10.1148/radiol.2472061331
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Hepatocellular Carcinoma in the Cirrhotic Liver: Challenges and Controversies

Abstract: The incidence of hepatocellular carcinoma (HCC) is expected to increase in the next 2 decades, largely due to hepatitis C infection and secondary cirrhosis. HCC is being detected at an earlier stage owing to the implementation of screening programs. Biopsy is no longer required prior to treatment, and diagnosis of HCC is heavily dependent on imaging characteristics. The most recent recommendations by the American Association for the Study of Liver Diseases (AASLD) state that a diagnosis of HCC can be made if a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
279
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(290 citation statements)
references
References 195 publications
3
279
2
6
Order By: Relevance
“…Hemodynamic alteration, such as microscopic arterioportal shunting around the treated HCC after RFA or TACE, or hypervascular enhancement around RFA representing inflammatory reactions to thermal injury, can occur (22,27). As described in several previous reports (2,3), we believe that this hemodynamic alteration owing to imageguided tumor therapy can resemble or mask HCCs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Hemodynamic alteration, such as microscopic arterioportal shunting around the treated HCC after RFA or TACE, or hypervascular enhancement around RFA representing inflammatory reactions to thermal injury, can occur (22,27). As described in several previous reports (2,3), we believe that this hemodynamic alteration owing to imageguided tumor therapy can resemble or mask HCCs.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, two observers achieved significantly higher Az values, diagnostic accuracies, sensitivities and negative predictive values when using gadoxetic acid-enhanced 3.0T MRI as compared to MDCT. The previously reported sensitivity of CT and MRI for the detection of small foci of residual or recurrent tumors after RFA ranged from 36-89% in the published literature (22). Several investigators have reported a sensitivity of 45-49% for the detection of HCC recurrence after TACE with CT scans combined with serum a-fetoprotein level (18,23).…”
Section: Discussionmentioning
confidence: 99%
“…The operative characteristics of CT are comparable, whereas MRI is more sensitive. The performance of CT and MRI is affected by the size of the lesions [204,205]. Although CT and MRI are reported to have a sensitivity of 60-94.4% and 58.5-93%, respectively, in tumors larger than 1 cm, their sensitivities for detecting tumors smaller than 1 cm are reduced by 33-45 and 33-67%, respectively [204,[206][207][208].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
“…If left alone, these tumors can grow aggressively and invasion can occur before tumors reach the 2-cm cutoff size for small HCC [202]. Thus, every attempt, including imaging follow-up or biopsy, should be made to characterize these nodules [205].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation